The Effect of Computer Use on Job Quality: Evidence from Europe - Seetha Menon; Andrea Salvatori; Wouter Zwysen (Institute of Labor Economics (IZA), 2018)
This paper studies changes in computer use and job quality in the EU-15 between 1995 and 2015. We document that while the proportion of workers using computers has increased from 40% to more than 60% over twenty years, there remain significant differences between countries even within the same occupations. Several countries have seen a significant increase in computer use even in low-skilled occupations generally assumed to be less affected by technology. Overall, the great increase in computer use between 1995 and 2015 has coincided with a period of modest deterioration of job quality in the EU-15 as whole, as discretion declined for most occupational and educational groups while intensity increased slightly for most of them. Our OLS results that exploit variation within country-occupation cells point to a sizeable positive effect of computer use on discretion, but to small or no effect on intensity at work. Our instrumental variable estimates point to an even more benign effect of computer use on job quality. Hence, the results suggest that the (moderate) deterioration in the quality of work observed in the EU-15 between 1995 and 2015 has occurred despite the spread of computers, rather than because of them.
Keywords: J21; J23; J24; O33; 330; job polarisation; job quality; tasks; discretion; intensity